The Influence of Professional Commitment, Machiavellian Attitude and Seriousness of Fraud on Whistleblowing Intentions with Locus of Control as Moderating - Fahyunah; Elvin Bastian; Iis Ismawati (Indonesian Journal of Economic & Management Sciences, 2024)
The research aims to determine the influence of professional commitment, Machiavellian attitude, seriousness of fraud on whistleblowing intentions with locus of control as a moderating variable. This research uses quantitative methods with descriptive and causal designs. The research sample was 52 school supervisors in the Education and Culture KCD of Banten Province, Cilegon City, Serang City and Regency, which were determined using a saturated sampling technique. The results show the influence of professional commitment, Machiavellian attitude, seriousness of fraud on whistleblowing intentions with locus of control as a moderating variable of 87.6%. Furthermore, professional commitment, Machiavellian attitude, seriousness of fraud have a positive effect on whistleblowing intentions. Locus of control moderates the influence of Machiavellian attitudes on whistleblowing intentions, but does not moderate the influence of professional commitment on whistleblowing intentions and does not moderate the influence of the seriousness of fraud on whistleblowing intentions